Factors leading to online purchase intention on facebook and instagram of generation Z - Mohd Sayadi, Shahirah Amira; Sidek, Shafie; Ismail, Kamarulzaman; Manickiam, Neelamehan; Thanasegaran, Ganesh; Jantan, Amer Hamzah (Hampstead Psychological Associates, 2020)
The purpose of this study is to examine factors leading to online purchase intention on Facebook and Instagram of Generation Z. This study is significant in at least two ways. First, it extends the work. Second, it provides information to organization such as marketers on ways to improve customer of Generation Z satisfaction. The sample size of the study consisted of 168 respondents that have experience shopping online. Four influencing factors (perceived ease of use, perceived usefulness, subjective norm and media richness) were examined on online purchase intention. The results of simple regression analysis reveal that three factors (perceived ease of use, perceived usefulness and media richness) have significant and positive impact on online purchase intention.